Religion would be a missing link in the case formulation of adolescents with conduct problems: an eclectic approach - Goker, Zeynep (Frontiers in Psychiatry, 2024)
Psychiatry is concerned with mental health. Cognition is one of the key mental functions and manifests itself primarily as behavior. A behavior exhibited in response to a stimulus is influenced by biological (inherited), psychological (individual), and social (environmental) factors. During consolidation of an exhibited behavior, the factors affecting the individual's cognitive structure and personality play crucial roles. Underlying factors for a problematic behavior, and their weakness/strength levels are determined via the Biopsychosocial model. Empirically effective current practices to intervene the problematic behaviors do not always result in success. One of the reasons may be other elements that were omitted during the case formulation process. This article aims to stress the idea that whatever the underlying factor of a problematic behavior is, the most crucial determinant and/or pre-emptive factor in developing or maintaining that behavior might actually be the religion as a governing and directive philosophy on how to conduct oneself. In this instance, the key is in the hands of the parents or caregivers.